Urinary neutrophil gelatinase‐associated lipocalin levels predict cisplatin‐induced acute kidney injury better than albuminuria or urinary cystatin C levels. Issue 6 (11th January 2013) - Lin, Hugo You‐Hsien; Lee, Su‐Chu; Lin, Sheng‐Fung; Hsiao, Hui‐Hua; Liu, Yi‐Chang; Yang, Wen‐Chi; Hwang, Daw‐Yang; Hung, Chi‐Chih; Chen, Hung‐Chun; Guh, Jinn‐Yuh
Abstract: Cisplatin‐induced acute kidney injury (AKI) is a major concern among clinicians in prescribing cisplatin‐based chemotherapy. This study evaluated and compared the ability of urinary biomarkers, including urinary neutrophil gelatinase‐associated lipocalin (NGAL), cystatin C, and the urinary albumin to creatinine ratio (ACR) to predict cisplatin‐induced AKI. Thirty‐three cancer patients receiving cisplatin‐based chemotherapy were prospectively studied, including 10 (30%) who developed AKI (the study group). Changes of urinary biomarkers were compared at 4 hours, 8 hours, and 12 hours, and 1 day, 2 days, 3 days, and 4 days after cisplatin intravenous infusions (75 mg/m 2 ) versus the baseline. There was a significant increase in urinary NGAL levels from 12 hours to 4 days ( p < 0.05) compared to baseline after cisplatin infusion in the AKI group. The magnitude of these changes over time differed significantly by group ( p < 0.001). The area under the receiver operating curve describing the relationship between urinary NGAL levels and AKI within 12 hours was 0.865 (95% confidence interval = 0.691–1.000). Urinary NGAL levels independently predicted AKI 12 hours after cisplatin ( p = 0.045) after adjustments for age, gender, body mass index, baseline serum creatinine, and urinary total protein. Urinary NGAL levels may be an early biomarker of AKI in patients receiving cisplatin‐based treatment.